Estudio socioeconómico de los vendedores y satisfacción de los usuarios de las ferias libres, como canal tradicional de comercialización en el cantón Paltas, año 2024 - Torres Rosario, Rashel Anayeli (2024)
The main objective of this research is to "Determine the socioeconomic level of vendors and the satisfaction of users of free fairs as a traditional marketing channel in the Paltas canton, 2024." In this context, free fairs, as traditional marketing channels, are essential for the local economy, offering a wide variety of fresh products and second-hand items. The study was conducted using a quantitative approach, which allowed for the collection and analysis of detailed information on the income, living conditions, and other economic aspects of the vendors, as well as evaluating user satisfaction with the products and services offered at the free fairs. The research design of this work is based on exploratory and descriptive research. This approach combines elements of both methodologies to address the study of the socioeconomic level of vendors and user satisfaction at the free fairs in the Paltas canton. For the sampling design, a simple random probability sampling technique will be used. This will allow us to cover a quite representative sample, including 374 surveys administered to individuals who meet the following characteristics: users of the free fairs (residents and visitors) and 100 surveys administered to vendors at the free fairs in the Paltas canton. From the results obtained, we can state that in the socioeconomic study of vendors, the income is generally low, which makes it difficult to meet basic needs and save. Additionally, significant challenges such as high transportation costs and competition were identified, negatively affecting the profitability of their activities. In terms of infrastructure, considerable variety was observed, with many vendors operating under precarious conditions. Regarding user satisfaction, the variety and quality of products offered are positively valued.